Estudio de factibilidad para la creación de una empresa de servicios SPA & Estética en Yumbo, Valle (2014)
This project is a study on the feasibility of creating a service spa & aesthetics in Yumbo, Valle, which would provide services for relaxation, meditation, nutrition and beauty, allowing wom ento find one place physical and emotional well being. The feasibility study is structured by chapters; the first chapter is for the draft in which the problem statement, objectives, methodological design was carried out for the realization of the whole project and the primary and secondary sources of information will be found. The second chapter concerns the general aspects of setting in which details each of these. The third chapter is the study of market, where product identification, analysis of demand, supply analysis, price analysis and marketing and distribution of the products shown. Chapter four, technical study, refers to the general and specific conditions, such assize, location and engineering to be taken into account to start with the feasibility study. The fifth chapter is organizational, legal and environmental study. The last chapters deal with the analysis of financial statements, the results of each study, determining the feasibility of creating spa and beauty center Yumbo.